Acute leukaemia after busulphan. Issue 6101 (10th December 1977) - Stott, H; Fox, W; Girling, D J; Stephens, R J; Galton, D A
Abstract : During a double-blind study of two years' cytotoxic chemotherapy with busulphan or cyclophosphamide in patients who had had resection of carcinoma of the bronchus the long-term effects of these two drugs were also studied. Four of the 243 patients treated with busulphan developed leukaemia compared with none of the 234 treated with cyclophosphamide and none of the 249 on placebo. None of these four patients received radiotherapy or other cytotoxic chemotherapy before leukaemia was diagnosed, and all four were among the 19 patients who developed pancytopenia while taking busulphan, five to eight years before leukaemia became clinically apparent. These findings suggest that busulphan is leukaemogenic, though its mode of action is uncertain.